2014
DOI: 10.4081/ijas.2014.3144
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight and Eye Size in Female European Eel Kept in Fresh and Salt Water

Abstract: The eel is a catadromous fish which spends most of its life in freshwater and adults swim to the Sargasso Sea region to spawn. While preparing for the reproductive process, eels undergo a metamorphosis to become what is called silver eel; a process involving changes in the colour and weight of the body and an increase in the eye size. These are indicators of fish maturity and they facilitate the selection of fish for reproduction under controlled conditions. During this study, changes in the body weight (BW) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 27 publications
3
23
0
3
Order By: Relevance
“…The oocyte diameters observed in this study after 5 weeks of stimulating the female fish were larger (0.176 ± 0.018 mm) than those observed by other authors after 6 weeks of the experiment (0.109 ± 0.041 mm) in a study examining the effect of swimming on the size of oocytes (Palstra et al 2007). It may be concluded that hormonal treatment considerably accelerates the process of gamete maturation, which was also confirmed by a study conducted by Nowosad et al (2014). The oocytes obtained at the end of the experiment had diameters of up to 0.853 mm, while eggs of a similar size (0.763-0.930 mm) obtained by Pedersen (2003) were regarded as pre-ovulation eggs.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The oocyte diameters observed in this study after 5 weeks of stimulating the female fish were larger (0.176 ± 0.018 mm) than those observed by other authors after 6 weeks of the experiment (0.109 ± 0.041 mm) in a study examining the effect of swimming on the size of oocytes (Palstra et al 2007). It may be concluded that hormonal treatment considerably accelerates the process of gamete maturation, which was also confirmed by a study conducted by Nowosad et al (2014). The oocytes obtained at the end of the experiment had diameters of up to 0.853 mm, while eggs of a similar size (0.763-0.930 mm) obtained by Pedersen (2003) were regarded as pre-ovulation eggs.…”
Section: Discussionsupporting
confidence: 58%
“…The hormonal stimulation was started after the desired water salinity level was achieved using the method described by Nowosad et al (2014). After being taken out of the tanks, the fish were put in a container with an anesthetic.…”
Section: Hormonal Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from reports published to date, along with the authors' own research (PALSTRA et al 2005;HORVÁTH et al, 2011;NOWOSAD et al 2014NOWOSAD et al , 2015, indicate that the effectiveness of artificial reproduction of eel depends closely on the maturity of gonads. The maturity of ovaries in eel can be determined by biopsy or by such indicators as an increase in body weight index -BWI (NOWOSAD et al 2014.…”
Section: Biopsymentioning
confidence: 99%
“…The maturity of ovaries in eel can be determined by biopsy or by such indicators as an increase in body weight index -BWI (NOWOSAD et al 2014.…”
Section: Biopsymentioning
confidence: 99%